Evaluation of durability against wetting and drying cycles of cement-natural rubber latex stabilised unpaved road under cyclic tensile loading. Issue 12 (15th October 2022) - Udomchai, Artit; Buritatum, Apinun; Suddeepong, Apichat; Hoy, Menglim; Horpibulsuk, Suksun; Arulrajah, Arul; Horpibulsuk, Jitwadee
ABSTRACT: Cement stabilised unpaved roads have been implemented worldwide in both developed and developing countries. In this research project, natural rubber latex (NRL) was used to improve the durability against wetting and drying (w-d) cycles of cement stabilised soil, under cyclic tensile loads. The influences of NRL replacement ratio on the indirect tensile strength (ITS), indirect tensile resilient modulus (IT Mr), and indirect tensile fatigue life (ITFL) prior to and after w-d cycles were studied. Cement-NRL stabilised soil was found to have superior resilient properties to minimise the plastic deformation and prevent sudden damage against the repetitive tensile stresses. The NRL replacement could improve the durability against w-d cycles of cement stabilised soil whereby the highest ITS, IT Mr, and ITFL were found at the optimum NRL replacement ratio of 20% for all number of w-d cycles tested. NRL was found to enhance the service life of cement stabilized soil as an unpaved material against fatigue cracking failure. The outcome of this research will promote the usage of NRL, which is available in plentiful supply in Thailand and other Southeast Asian and South American countries, as a sustainable additive in pavement applications.